IDENTIFIKASI BENTENG TAKIMPO LIPUOGENA DI KELURAHAN TAKIMPO KECAMATAN PASARWAJO KABUPATEN BUTON - Hasanah Kaimuddin (Laboratorium Jurusan Arkeologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2018)
This study aims to know what are the remains contained in the Takimpo Lipuogena fortress and its function based on the remains. This study used space archeology theory and settlement theory. This study apllied adescriptive method of data collection techniques in the form of literature studies which is means the collection ofliterature related to the title of the study, field observations with surface surveys and data recording and interviews,and the stages of data processing and contextual analysis. The results showed that the archaeological remains of Takimpo Lipuogena fort were in the form of baruga,mosque, inauguration stone, turtle stone, flagpole holes, the stones for burned some candles, reconnaissance holes (miserly holes) and graves. Takimpo Lipuogena was originally built as a village or Kadie based on the orders fromsultanate of Buton. The goal of build the Takimpo Lipuogena Fortress was as a Bhonto or surveillance. then duringthe reign of Sultan Anharuddin in 1822-1823, society in Takimpo Lipuogena fort formed a defense force with theassistance of the sultanate led by Muh. Idrus Kaimuddin to expel the pirates named Tobelo. After Muh. IdrusKaimuddin succeeded in driving away Tobelo, the society of Takimpo Lipuogena rebuilt the settlements in TakimpoLipuogena fort. The society utilized the fort as a plantation and spring as a daily necessity for them which is still usedby the community in Takimpo Village until today.